FENOMENA PERJODOHAN DI PONDOK PESANTREN SERTA IMPLIKASINYA TERHADAP KELUARGA SAKINAH - Ramadhan, Mufti (Universitas Islam Negeri Antasari Banjarmasin, 2024)
Abstract: This research discusses the phenomenon of arranged marriages in Islamic boarding schools and its implications for the Sakinah family based on the Decree of the Minister of Religion of the Republic of Indonesia Number 3 of 1999 concerning the Development of the Sakinah Family Movement. This type of research is field research which is descriptive qualitative in nature. The subjects of this research were married alumni and kiyais who were making matches. Meanwhile, the object of this research is a general description of the phenomenon of arranged marriages in Islamic boarding schools and its implications for the Sakinah family. Data collection was carried out by data mining, the author used observation, interviews and documentation techniques. Meanwhile, data processing techniques are carried out by editing, verification and analysis. Based on the research results, it is known that the Arranged Marriage Phenomenon has been realized up to now based on the efforts and role of the Chairman to match his students and the good response of his students to the matchmaking, and this matchmaking has good implications and is included in sakinah III plus based on the benchmarks stated in the letter Decree of the Minister of Religion of the Republic of Indonesia number 03 in 1999 concerning the development of the Sakinah family movement. Keywords: Phenomenon, Arranged Marriage, Sakinah Abstrak : Penelitian ini membahas tentang Fenomena Perjodohan di Pondok Pesantren serta Implikasinya Terhadap Keluarga Sakinah berdasarkan Keputusan Menteri Agama Republik Indonesia Nomor 3 Tahun 1999 Tentang Pembinaan Gerakan Keluarga Sakinah. Jenis penelitian ini adalah penelitian mix method yaitu lapangan (field research) dan normatif yang bersifat diskriptif kualitatif. Subjek penelitian ini adalah alumni yang sudah menikah serta para kiyai yang menjodohkan. Sedangkan objek dalam penelitian ini adalah gambaran umum tentang fenomena perjodohan di Pondok Pesantren serta implikasinya terhadap keluarga sakinah. Hasil dari penelitian ini, diketahui bahwa Fenomena Perjodohan terealisasi sampai sekarang berdasarkan upaya dan peran kiyayi untuk menjodohkan para Santrinya dan respon baik dari santri-santrinya terhadap perjodohan tersebut, serta perjodohan ini berimplikasi baik dan termasuk sakinah III plus berdasarkan tolak ukur yang di tertera dalam surat keputusan menteri agama republik Indonesia pada nomor 03 pada tahun 1999 tentang pembinanan gerakan keluarga sakinah. Kata kunci: Fenomena, Perjodohan, implikasi keluarga Sakinah